Productivity of red clover varieties in conditions of the Middle Urals - N. I. Kasatkina; Zh. S. Nelyubina (Аграрная наука Евро-Северо-Востока, 2016)
Field experiments were carried out on sod-podzolic medium-loamy soils typical for Middle Urals in order to estimate the fodder and seed production of red clover varieties depending on abiotic conditions and herbage age. Meteorological conditions in the years of research (2011-2015) were different and had a significant impact on the clover productivity. The average varietal yield of dry aboveground mass of red clover of the first year of use in a sum of two mowings was 7.2-7.4 t / ha; in the second year of use dry matter yield was at level of 6.3-6.7 t / ha. Relatively hot and humid growing season of 2012 contributed to the formation of high forage productivity of clover herbage in 1st (8.2 t / ha) and 2nd year of use (10.4-10.6 t / ha). The average varietal yield of clover seeds in 1st year of use ranged from 40-55 kg / ha in a cool and wet growing season up to 259-282 kg / ha at a relatively hot and dry weather. The long-term average varietal yield (average yield in the experiment) of clover varieties of double-cut type was 157 kg / ha, single-cut type - 147 kg / ha. In the 2nd year of herbage use, the seed productivity of red clover decreased up to 39 and 38 kg / ha, respectively. On average for the research, the high fodder productivity was formed by varieties Dymkovskyi, Pamyaty Burlaki, and Onyx. Green mass of clover had high nutritional value and corresponded to zootechnical standards. The seed productivity of studied varieties of clover was on the level of standard varieties.